(untitled) (Journal of Forestry, 2024)
One of the most time-consuming stages in the production of coniferous trees is debarking the bark of the product. During debarking with a chainsaw apparatus, many air pollutants such as bark residues, dust, sawdust, fuel material, etc. are mixed into the environment. This situation reduces the air quality for the workers. This study aims to investigate the impact of the debarking process on worker health and environmental impacts in coastal pine plantations in Sarıyer region. The air pollution parameters PM2.5, PM10, CO2 and HCHO levels during the debarking process were measured using a Temtop M2000 air quality meter. The results showed that when comparing these values to standard air quality metrics, it’s clear that the peak values of PM2.5, PM10, and CO2 (247 μg/m3, 411 μg/m3, and 2549 ppm) result in a "Very Unhealthy" environment. The average values for all three (83.91 μg/m3, 121.69 μg/m3, and 614.19 ppm) are classified as "Unhealthy" for PM2.5, and "Moderate" for PM10 and CO2. The study results emphasize that the log debarking process is associated with bark volume, CO2 release and PM2.5 levels. Therefore, it is vital that workers in harvesting use maximum protective equipment, especially respirators. There is also a need to raise awareness and provide training for forest workers on the use of protective equipment. These findings may contribute to the development of effective policies on the health of workers in wood production and environmental quality.